2022
DOI: 10.1021/acsami.1c19033
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Three-Dimensional Mo2C/NC@MXene and Its Efficient Electromagnetic Absorption Properties

Abstract: The positively charged MoO 3 /PDA microspheres are obtained by stacking and assembly of the sheet structure, and the negatively charged MXene nanosheets are wrapped on the surface through the principle of electrostatic self-assembly. After annealing, a nitrogen-doped carbon composite and a MXene-coated Mo 2 C wave absorber are obtained. The formation of the wrinkled surface provides a complex pore structure, and the multiple interface reflections between the nanosheets enhance the absorption performance. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…By comparison, it could be seen that when the content of Ag particles in nanocomposites was low, it had better electromagnetic wave absorption performance. The absorptive properties of composites recently reported in the literature studies were compared (Figure S9), and the comparison showed that S-MXene (TiO 2 )/Ag/CoNi nanocomposites exhibited better absorbing properties and greater application prospects than other reported materials. The effective bandwidth of S1-45 wt % at a thickness of 2.4 mm was 5.6 GHz, and the minimum reflection loss of −80.9 dB (S3-55 wt %) could be achieved after adjusting the component content.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, it could be seen that when the content of Ag particles in nanocomposites was low, it had better electromagnetic wave absorption performance. The absorptive properties of composites recently reported in the literature studies were compared (Figure S9), and the comparison showed that S-MXene (TiO 2 )/Ag/CoNi nanocomposites exhibited better absorbing properties and greater application prospects than other reported materials. The effective bandwidth of S1-45 wt % at a thickness of 2.4 mm was 5.6 GHz, and the minimum reflection loss of −80.9 dB (S3-55 wt %) could be achieved after adjusting the component content.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the previous work, 31 MXene was obtained by etching with concentrated hydrochloric acid (HCl, 36–37%, Sinopharm Chemical Reagent Co. Ltd) and lithium fluoride (LiF, 99%, Sinopharm Chemical Reagent Co., Ltd). First, 10 mL MXene was dispersed in 70 mL deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…In the meanwhile, the defect sites are formed around the pore edges, which can serve as the polarization sites to increase the polarization losses of 3D HPCs and improve the EMW absorption performance. [8][9][10] Furthermore, the large pore volume endows the 3D HPCs with a low mass density, which benefits to the construction of lightweight EMW absorbers. [11] Nevertheless, a further improvement of the dielectric losses in 3D HPCs with the aim of enhancing the EMW absorption performance of related materials still faces a huge challenge due to a lack of sufficient polarizable centers.…”
Section: Research Articlementioning
confidence: 99%